2020
DOI: 10.3390/jcm9061680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 99mTc-Labeled Colloid SPECT/CT and Planar Lymphoscintigraphy in Sentinel Lymph Node Detection in Patients with Melanoma: A Meta-Analysis

Abstract: We compared the detection rate (DR) for sentinel lymph nodes (SLNS), the number of SLNs and the subjects with additional SLNs of single-photon emission computed tomography (SPECT/CT) and planar lymphoscintigraphy (PL) in patients with melanoma. Furthermore, we evaluated the impact of SPECT/CT on surgical plans. Articles containing head-to-head comparisons between SPECT/CT and PL were searched in Pubmed/MEDLINE and Scopus. The literature search was updated until December 31st, 2019. DR was calculated on a per-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…23 A recent meta-analysis demonstrated a higher overall SLN detection rate and proportion of patients with additional SLNs. 24 Another study highlighted the health economic benefit of this approach. 25 Our data are consistent with the previous literature in that we found a significantly increased number of SLNs and were identified by SPECT/ CT compared with LSG (median 3 vs. 2; p \ 0.0001) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent meta-analysis demonstrated a higher overall SLN detection rate and proportion of patients with additional SLNs. 24 Another study highlighted the health economic benefit of this approach. 25 Our data are consistent with the previous literature in that we found a significantly increased number of SLNs and were identified by SPECT/ CT compared with LSG (median 3 vs. 2; p \ 0.0001) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoscintigraphy is currently the ‘gold standard’ imaging technique for the diagnosis of extremity lymphedema when the clinical diagnosis is uncertain and, indeed, provides a clear image of the lymphatic drainage status of the upper limb [ 37 , 38 ]. Lymphoscintigraphy involves injection of a radiotracer in the hand and analysis of proximal lymph node uptake.…”
Section: Diagnosis Of Bcrl and Clinical Symptomsmentioning
confidence: 99%
“…Some centers have reported also quantitative analysis based on decay-adjusted uptake and lymphatic transport index; however these are not commonly performed [ 39 , 40 ]. Recently, single photon emission computed tomography-computed tomography (SPECT-CT) lymphoscintigraphy has been used for the diagnosis of lymphedema providing 3-D live images of lymph flow [ 38 , 41 , 42 ]. A recent study reported significant association between the type of dermal backflow, the lymph flow pathways, and the visualization of lymph nodes around the clavicle [ 42 ].…”
Section: Diagnosis Of Bcrl and Clinical Symptomsmentioning
confidence: 99%
“…In addition to melanoma and breast cancer, SNL lymphoscintigraphy is used and investigated in surgical planning applications for multiple malignancies including head and neck, valvular, cervical, and prostate cancers [ 75 , 76 , 77 , 78 , 79 , 80 ]. Utilizing SPECT/CT with lymphoscintigraphy improves anatomical localization and detection rate of lymphoscintigraphy [ 81 , 82 ]. Multiple factors can affect lymphoscintigraphy including BMI, age, and tumor location.…”
Section: Radiologic Evaluation Of the Lymphatic System In Cancer Patientsmentioning
confidence: 99%